Midwife-led birthing centres in Bangladesh, Pakistan and Uganda: an economic evaluation of case study sites - AKM Fazlur Rahman; Oliva Bazirete; Emily J Callander; Abdul Halim; Abu Sayeed Abdullah; Caroline Homer; Andrea Nove; Sabera Turkmani; Mandy Forrester; Alayna Carrandi; Sally Pairman; Scovia Nalugo Mbalinda; et al. (BMJ Global Health)
Introduction Achieving the Sustainable Development Goals to reduce maternal and neonatal mortality rates will require the expansion and strengthening of quality maternal health services. Midwife-led birth centres (MLBCs) are an alternative to hospital-based care for low-risk pregnancies where the lead professional at the time of birth is a trained midwife. These have been used in many countries to improve birth outcomes.Methods The cost analysis used primary data collection from four MLBCs in Bangladesh, Pakistan and Uganda (n=12 MLBC sites). Modelled cost-effectiveness analysis was conducted to compare the incremental cost-effectiveness ratio (ICER), measured as incremental cost per disability-adjusted life-year (DALY) averted, of MLBCs to standard care in each country. Results were presented in 2022 US dollars.Results Cost per birth in MLBCs varied greatly within and between countries, from US$21 per birth at site 3, Bangladesh to US$2374 at site 2, Uganda. Midwife salary and facility operation costs were the primary drivers of costs in most MLBCs. Six of the 12 MLBCs produced better health outcomes at a lower cost (dominated) compared with standard care; and three produced better health outcomes at a higher cost compared with standard care, with ICERs ranging from US$571/DALY averted to US$55 942/DALY averted.Conclusion MLBCs appear to be able to produce better health outcomes at lower cost or be highly cost-effective compared with standard care. Costs do vary across sites and settings, and so further exploration of costs and cost-effectiveness as a part of implementation and establishment activities should be a priority.